Polyimide, polyimide solution, polyimide film, adhesive film, laminate, coverlay film, resin-coated copper foil, metal-clad laminate, circuit board, and multi-layer circuit board
Patent Information
- Application Number
- JP2020164842
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-09-30
AI Technical Summary
【0035】 本発明のポリイミドは、脂肪族ジアミンを原料とするポリイミド中に含まれるフッ素原子の量が制御されているため、これをフィルム化することによって、優れた接着性を有しながら、誘電正接が顕著に低いポリイミドフィルムを形成できる。 従って、本発明のポリイミドフィルムは、周波数がGHz帯域(例えば1~20GHz)の高周波信号を伝送する回路基板等へ適用した場合に、高周波信号伝送における伝送損失を効果的に低減することが可能となる。
Smart Images

Figure 0007636149000006 
Figure 0007636149000007 
Figure 0007636149000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide useful as a material for electronic components, and to an adhesive film, a laminate, a coverlay film, a resin-coated copper foil, a metal-clad laminate, a circuit board, and a multilayer circuit board each using the polyimide. [Background technology]
[0002] In recent years, with the progress of miniaturization, weight saving, and space saving of electronic devices, there is an increasing demand for flexible printed circuits (FPCs) that are thin, lightweight, flexible, and have excellent durability even when repeatedly bent. Because FPCs allow three-dimensional and high-density mounting even in a limited space, their applications are expanding to include wiring for moving parts of electronic devices such as HDDs, DVDs, and smartphones, as well as components such as cables and connectors.
[0003] One embodiment of FPC is a structure in which a circuit pattern is formed on a polyimide film having excellent heat resistance and flexibility, and a coverlay film having an adhesive layer is laminated to the surface of the polyimide film. Polyimide is used as the material for the adhesive layer of the coverlay film having such a structure. For example, it has been proposed to apply a crosslinked polyimide obtained by reacting a polyimide made from an aliphatic diamine compound derived from a dimer acid with an amino compound having at least two primary amino groups as functional groups to the adhesive layer of the coverlay film (for example, Patent Document 1).
[0004] In addition, in a three-layer metal-clad laminate, which is a material for circuit boards such as FPCs, in which a metal layer to be wired is bonded to an insulating resin layer via an adhesive layer, it has been proposed to use a polyimide containing a predetermined amount or more of aliphatic diamine residues derived from a dimer diamine in which the two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups, in the adhesive layer (for example, Patent Document 2).
[0005] In addition to the above-mentioned high density, the performance of devices has improved, and so it is also necessary to deal with higher frequencies of transmission signals. When transmitting high-frequency signals, if the transmission loss in the transmission path is large, inconveniences such as loss of electrical signals and longer signal delay times occur. Therefore, in the future, it will be important to reduce transmission loss in FPCs as well. For this reason, in a circuit board having a polyimide insulating layer, a circuit wiring layer laminated on at least one surface of the polyimide insulating layer, and a coverlay film laminated on the circuit wiring layer, it has been proposed to take into consideration the relationship between the thickness, relative dielectric constant, and dielectric loss tangent of the polyimide insulating layer and the coverlay film (for example, Patent Document 3). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-1730 A [Patent Document 2] JP 2018-140544 A [Patent Document 3] JP 2016-192531 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described in Patent Documents 1 and 2, adhesive layers using polyimides derived from aliphatic diamines exhibit excellent adhesion and low dielectric constants and dielectric dissipation factors, but further improvements in dielectric properties are required to accommodate the increasing frequencies of transmission signals.
[0008] Therefore, an object of the present invention is to further improve the dielectric properties of an adhesive layer using a polyimide made from an aliphatic diamine, and to more effectively reduce the transmission loss of high frequency signals. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that the dielectric properties of polyimide can be significantly improved by introducing a residue having a fluorine atom into polyimide using an aliphatic diamine as a raw material and controlling the content of fluorine atoms, thereby completing the present invention.
[0010] The polyimide of the present invention is a polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component. a) containing a fluorine atom-containing tetracarboxylic acid residue and / or a fluorine atom-containing diamine residue, and the total content of the fluorine atoms relative to the total content of all atoms in the polyimide is within the range of 1% by weight or more and 20% by weight or less; b) containing 40 mol % or more of diamine residues derived from aliphatic diamines based on the total diamine residues; c) being a thermoplastic polyimide; The present invention is characterized in that:
[0011] The polyimide of the present invention may be a dimer diamine composition in which the aliphatic diamine is a dimer diamine obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups as a main component.
[0012] The polyimide of the present invention may have a weight average molecular weight in the range of 5,000 to 200,000.
[0013] The polyimide of the present invention may have a content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) in the total content of all atoms in the polyimide within a range of 12 to 40% by weight.
[0014] The polyimide of the present invention is represented by the following formula (i): CM value = (C / Mw) x 10 4 (i) [In the formula, C represents the weight content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide, and Mw represents the weight average molecular weight of the polyimide.] The CM value, which is an index representing the amount of six-membered aromatic rings contained in the polyimide, may be within the range of 3 to 38, as calculated based on the above formula:
[0015] The polyimide solution of the present invention contains any one of the polyimides described above and a solvent capable of dissolving the polyimide.
[0016] The polyimide film of the present invention is a polyimide film containing, as a resin component, a polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component. In the polyimide film of the present invention, the polyimide contains a tetracarboxylic acid residue containing a fluorine atom and / or a diamine residue containing a fluorine atom, and the total content of the fluorine atoms is in the range of 1% by weight to 20% by weight based on the total content of all atoms in the polyimide. The polyimide film of the present invention may have a dielectric loss tangent (Tan δ) of less than 0.002 at 10 GHz measured with a split post dielectric resonator (SPDR) after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23° C. and 50% RH.
[0017] In the polyimide film of the present invention, the polyimide may contain 40 mol % or more of diamine residues derived from aliphatic diamines based on the total diamine residues.
[0018] In the polyimide film of the present invention, the aliphatic diamine may be a dimer diamine composition mainly composed of a dimer diamine obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups.
[0019] In the polyimide film of the present invention, the weight average molecular weight of the polyimide may be within the range of 5,000 to 200,000.
[0020] In the polyimide film of the present invention, the content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide may be within a range of 12 to 40% by weight.
[0021] The polyimide film of the present invention has a molecular weight of 1.0 or more and a molecular weight of 1.0 or more. CM value = (C / Mw) x 10 4 (i) [In the formula, C represents the weight content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide, and Mw represents the weight average molecular weight of the polyimide.] The CM value, which is an index representing the amount of six-membered aromatic rings contained in the polyimide, may be within the range of 3 to 38, as calculated based on the above formula:
[0022] The adhesive film of the present invention comprises the above-mentioned polyimide film.
[0023] The laminate of the present invention is a laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, characterized in that the adhesive layer is made of the above-mentioned adhesive film.
[0024] The coverlay film of the present invention is a coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, characterized in that the adhesive layer is made of the above-mentioned adhesive film.
[0025] The resin-coated copper foil of the present invention is a resin-coated copper foil having an adhesive layer and a copper foil laminated thereon, characterized in that the adhesive layer is made of the above-mentioned adhesive film.
[0026] The metal-clad laminate of the present invention is a metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, and is characterized in that at least one of the insulating resin layers is made of the above-mentioned adhesive film.
[0027] The metal-clad laminate of the present invention comprises an insulating resin layer, an adhesive layer laminated on at least one surface of the insulating resin layer, and Agent and a metal layer laminated on the insulating resin layer via an adhesive layer, wherein the adhesive layer is made of the above-mentioned adhesive film.
[0028] The metal-clad laminate of the present invention includes a first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one surface of the second metal layer; An adhesive layer is arranged so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate, The adhesive layer is characterized by being made of the above adhesive film.
[0029] The metal-clad laminate of the present invention comprises a single-sided metal-clad laminate having an insulating resin layer and a metal layer laminated on one side of the insulating resin layer, and an adhesive layer laminated on the other side of the insulating resin layer, wherein the adhesive layer is made of the above-mentioned adhesive film.
[0030] The circuit board of the present invention is obtained by wiring the metal layer of the metal-clad laminate.
[0031] The circuit board of the present invention is a circuit board comprising a first base material, a wiring layer laminated on at least one surface of the first base material, and an adhesive layer laminated on the surface of the first base material facing the wiring layer so as to cover the wiring layer, and is characterized in that the adhesive layer is made of the above-mentioned adhesive film.
[0032] The circuit board of the present invention is a circuit board comprising a first substrate, a wiring layer laminated on at least one surface of the first substrate, an adhesive layer laminated on the surface of the first substrate facing the wiring layer so as to cover the wiring layer, and a second substrate laminated on the surface of the adhesive layer opposite the first substrate, wherein the adhesive layer is made of the adhesive film described above.
[0033] The circuit board of the present invention is a circuit board comprising a first substrate, an adhesive layer laminated on at least one side of the first substrate, a second substrate laminated on the side of the adhesive layer opposite the first substrate, and wiring layers laminated on the sides of the first substrate and the second substrate opposite the adhesive layer, respectively, wherein the adhesive layer is made of the adhesive film described above.
[0034] The multilayer circuit board of the present invention is a multilayer circuit board including a laminate including a plurality of laminated insulating resin layers, and at least one wiring layer embedded in the laminate, At least one of the plurality of insulating resin layers is formed of an adhesive layer having adhesive properties and covering the wiring layer, and the adhesive layer is made of the adhesive film. Effect of the Invention
[0035] The polyimide of the present invention is made from an aliphatic diamine as a raw material, and the amount of fluorine atoms contained therein is controlled. Therefore, by forming this polyimide into a film, a polyimide film having excellent adhesion and a remarkably low dielectric tangent can be formed. Therefore, when the polyimide film of the present invention is applied to a circuit board or the like that transmits high-frequency signals in the GHz frequency band (for example, 1 to 20 GHz), it becomes possible to effectively reduce transmission loss in high-frequency signal transmission. [Brief description of the drawings]
[0036] [Figure 1] 1 is a schematic diagram showing a cross-sectional configuration of a laminate according to an embodiment of the present invention. [Diagram 2] 1 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to an embodiment of the present invention. [Diagram 3] FIG. 4 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to another embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram showing a cross-sectional configuration of a metal-clad laminate according to yet another embodiment of the present invention. [Diagram 5] 1 is a schematic diagram showing a cross-sectional configuration of a circuit board according to an embodiment of the present invention; [Figure 6] FIG. 13 is a schematic diagram showing a cross-sectional configuration of a circuit board according to another embodiment of the present invention. [Figure 7] FIG. 13 is a schematic diagram showing a cross-sectional configuration of a circuit board according to still another embodiment of the present invention. [Figure 8] 1 is a schematic diagram showing a cross-sectional configuration of a multilayer circuit board according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the accompanying drawings.
[0038] The polyimide according to one embodiment of the present invention is a polyimide having adhesive properties. Hereinafter, the polyimide according to the present embodiment may be referred to as "adhesive polyimide". The adhesive polyimide contains a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component. In the present invention, the "tetracarboxylic acid residue" refers to a tetravalent group derived from a tetracarboxylic acid dianhydride, and the "diamine residue" refers to a divalent group derived from a diamine compound. When the raw materials tetracarboxylic acid anhydride and diamine compound are reacted in approximately equal moles, the types and molar ratios of the tetracarboxylic acid residues and diamine residues contained in the polyimide can be approximately corresponding to the types and molar ratios of the raw materials. In the present invention, the term "polyimide" refers to a resin made of a polymer having an imide group in the molecular structure, such as polyimide, polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, polybenzimidazoleimide, etc.
[0039] The adhesive polyimide is a polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component, and satisfies the following conditions a to c.
[0040] a) The polyimide contains a tetracarboxylic acid residue containing a fluorine atom (fluorine-containing tetracarboxylic acid residue) and / or a diamine residue containing a fluorine atom (fluorine-containing diamine residue), and the total content of the fluorine atoms relative to the total content of all atoms in the polyimide is 1% by weight or more and 20% by weight or less. The adhesive polyimide contains a fluorine-containing tetracarboxylic acid residue and / or a fluorine-containing diamine residue, and the total content of fluorine atoms relative to the total content of all atoms in the adhesive polyimide is controlled to be in the range of 1% by weight to 20% by weight, preferably 1% by weight to 15% by weight, more preferably 1% by weight to 12% by weight. If the total content of fluorine atoms is less than 1% by weight, the effect of lowering the dielectric tangent is not obtained, and if it exceeds 20% by weight, the amount of residues derived from aliphatic diamines is relatively small, resulting in a decrease in adhesiveness, and thus impairing thermocompression processability. The reason why the dielectric tangent is lowered by setting the content of fluorine atoms within the above range has not yet been fully elucidated, but it is presumed that this is because fluorine atoms are highly hydrophobic and low polar, and in combination with aliphatic diamines with high molecular mobility, the introduction of bulky fluorine substituents can be expected to have an effect of suppressing molecular mobility, thereby lowering the dielectric tangent. In addition, the adhesive polyimide of the present embodiment uses an aliphatic diamine as the diamine compound of the raw material in order to maintain the adhesiveness and solvent solubility of a thermoplastic resin while lowering the dielectric tangent. By controlling the amount of the residue derived from the aliphatic diamine as well as the concentration of the fluorine atoms derived from the raw material monomer, it is possible to ensure a sufficient amount of the aliphatic diamine used and maintain the adhesiveness and solvent solubility of a thermoplastic resin while suppressing the dielectric tangent to an extremely low value.
[0041] The fluorine-containing tetracarboxylic acid residue may be an aromatic tetracarboxylic acid dianhydride residue or an aliphatic tetracarboxylic acid dianhydride residue as long as it is a residue of a tetracarboxylic acid dianhydride containing a fluorine atom, but in order to adjust the content of aromatic rings (aromatic ring concentration) contained in the adhesive polyimide and lower the dielectric tangent, it is preferable that it is an aromatic tetracarboxylic acid dianhydride residue containing a fluorine atom in the substituent. Examples of such tetracarboxylic acid dianhydrides include 4,4'-(2,2'-hexafluoroisopropylidene)diphthalic dianhydride (6FDA), (trifluoromethyl)pyromellitic dianhydride, di(trifluoromethyl)pyromellitic dianhydride, di(heptafluoropropyl)pyromellitic dianhydride, pentafluoroethylpyromellitic dianhydride, bis{3,5-di(trifluoromethyl)phenoxy}pyromellitic dianhydride, 5,5-di(trifluoromethyl) ... ,5'-Bis(trifluoromethyl)-3,3',4,4'-tetracarboxybiphenyl dianhydride, 2,2',5,5'-tetrakis(trifluoromethyl)-3,3',4,4'-tetracarboxybiphenyl dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxydiphenyl ether dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxybenzophenone dianhydride, Bis {(trifluoromethyl)dicarboxyphenoxy}benzene dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}trifluoromethylbenzene dianhydride, bis(dicarboxyphenoxy)trifluoromethylbenzene dianhydride, bis(dicarboxyphenoxy)bis(trifluoromethyl)benzene dianhydride, bis(dicarboxyphenoxy)tetrakis(trifluoromethyl)benzene dianhydride, 2,2-bis{4-(3,4-dicarboxyphenoxy)phenyl}hexafluoropropane dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}biphenyl dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}bis(trifluoromethyl)biphenyl dianhydride, bis{(trifluoromethyl)dicarboxyphenoxy}diphenyl ether dianhydride, bis(dicarboxyphenoxy)bis(trifluoromethyl)biphenyl dianhydride, and the like.These tetracarboxylic anhydrides may be used alone or in combination of two or more. Among the above fluorine atom-containing tetracarboxylic dianhydrides, from the viewpoints of high effect of imparting solvent solubility to polyimide, high content of fluorine atoms, and reactivity with diamine, it is preferable to use 6FDA, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxybiphenyl dianhydride, 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxydiphenyl ether dianhydride, and 5,5'-bis(trifluoromethyl)-3,3',4,4'-tetracarboxybenzophenone dianhydride, and it is more preferable to use 6FDA.
[0042] The fluorine-containing diamine residue is not particularly limited as long as it is a residue of a diamine compound containing a fluorine atom, and may be a residue of an aromatic diamine or an aliphatic diamine. However, in order to adjust the content of aromatic rings (aromatic ring concentration) contained in the adhesive polyimide and lower the dielectric tangent, it is preferable that the residue is an aromatic diamine containing a fluorine atom in the substituent. Examples of such aromatic diamines include 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP), 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), 3,4-diamino-2,2'-bis(trifluoromethyl)biphenyl, 1,4-bis(4-amino-2-trifluoromethylphenoxy ... Preferred are 4,4'-bis(2-(trifluoromethyl)-4-aminophenoxy)benzene, 4,4'-bis(2-(trifluoromethyl)-4-aminophenoxy)phenyl, 2,2-bis(4-(2-(trifluoromethyl)-4-aminophenoxy)phenyl)hexafluoropropane, 4,4'-bis(3-(trifluoromethyl)-4-aminophenoxy)biphenyl, p-bis(2-trifluoromethyl)-4-aminophenoxy]benzene, and 9,9-bis(3-fluoro-4-aminophenyl)fluorene. These diamine compounds may be used alone or in combination of two or more. Among the above diamine compounds containing fluorine atoms, it is preferable to use HFBAPP and 2,2-bis(4-(2-(trifluoromethyl)-4-aminophenoxy)phenyl)hexafluoropropane from the viewpoint of having a linear bond position that has a high effect of imparting solvent solubility to polyimide and a high effect of suppressing molecular motion, and it is more preferable to use TFMB from the viewpoint of increasing the content of fluorine atoms in polyimide.
[0043] b) The diamine residues derived from aliphatic diamines constitute 40 mol % or more of the total diamine residues. The dielectric constant and dielectric loss tangent of the polyimide can be reduced by setting the content of the diamine residue derived from the aliphatic diamine to 40 mol% or more, preferably 60 mol% or more, more preferably within the range of 60 to 99 mol%, and further preferably within the range of 70 to 90 mol% relative to the total diamine residues. When the content of the diamine residue derived from the aliphatic diamine is less than 40 mol%, the polar groups contained in the polyimide increase relatively, so that the dielectric constant and dielectric loss tangent tend to increase. In addition, by containing the diamine residue derived from the aliphatic diamine in the above amount, it is possible to improve the thermocompression bonding characteristics by lowering the glass transition temperature (lowering Tg) of the polyimide and to alleviate the internal stress by lowering the elastic modulus. On the other hand, when the content of the diamine residue derived from the aliphatic diamine exceeds 99 mol% relative to the total diamine residues, the mobility of the molecular chain of the polyimide is excessively increased, and the dielectric loss tangent may increase. In addition, as the aliphatic diamine, one containing a fluorine atom may be used, but it is preferable to use one not containing a fluorine atom. Details of the aliphatic diamine will be described later.
[0044] c) It is a thermoplastic polyimide. The thermoplasticity of the adhesive polyimide imparts high adhesiveness and thermocompression processability, making it possible to use it as an adhesive layer. Here, the term "thermoplastic polyimide" generally refers to a polyimide that can be softened by heating and solidified by cooling, and this process can be repeated, and has a clearly identifiable glass transition temperature. In the present invention, however, it refers to a polyimide whose glass transition temperature can be clearly confirmed in a temperature range of less than 150°C. From the viewpoint of thermocompression bonding at low temperatures, the thermoplastic polyimide is preferably a polyimide whose glass transition temperature can be clearly confirmed in a temperature range of less than 100°C, and has a storage modulus of 1.0×10 at 30°C measured using a dynamic mechanical elasticity measuring device (DMA). 8 Pa or more, and the storage modulus at the glass transition temperature +30°C is 1.0 x 10 7In contrast, the term "non-thermoplastic polyimide" refers to a polyimide that does not soften or exhibit adhesiveness even when heated, and in the present invention, the polyimide has a storage modulus of 1.0×10 at 30° C. as measured using a dynamic mechanical analyzer (DMA). 9 Pa or more, and the storage modulus at 300°C is 1.0 x 10 8 This means that it indicates Pa or higher.
[0045] The adhesive polyimide contains a certain amount or more of residues derived from an aliphatic diamine, and is therefore a solvent-soluble polyimide that is soluble in organic solvents such as N-methyl-2-pyrrolidone (NMP), and is suitable for use in the form of being applied to a substrate such as a metal foil.
[0046] It is preferable that the adhesive polyimide further satisfies the following conditions d to h.
[0047] Condition d) The content of carbon atoms derived from 6-membered aromatic rings (excluding carbon atoms of 6-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide is within a range of 12 to 40% by weight. The content of carbon atoms derived from 6-membered aromatic rings means the content of aromatic rings (aromatic ring concentration) contained in the adhesive polyimide. By setting the content of carbon atoms derived from 6-membered aromatic rings in the range of 12 to 40% by weight, molecular motion is restricted by the interaction between aromatic rings in the polyimide, and the effect of reducing dielectric tangent is exhibited. If the content of carbon atoms derived from 6-membered aromatic rings is less than 12% by weight, the motion of the molecular chain of the polyimide cannot be suppressed, and the dielectric tangent becomes high. If the content of carbon atoms derived from 6-membered aromatic rings exceeds 40% by weight, the polarity of the molecule becomes large, and the dielectric tangent becomes high. The content of carbon atoms derived from 6-membered aromatic rings is preferably in the range of 17 to 38% by weight, more preferably in the range of 20 to 30% by weight.
[0048] Condition e) The weight average molecular weight is within the range of 5,000 to 200,000. If the weight-average molecular weight of the adhesive polyimide is less than 5,000, the film tends to become brittle, whereas if the weight-average molecular weight is more than 200,000, the varnish tends to have a high viscosity and tends to have uneven thickness when coated. The weight-average molecular weight of the adhesive polyimide is preferably in the range of 10,000 to 60,000, more preferably in the range of 20,000 to 55,000. If the weight-average molecular weight is less than 10,000, the dielectric constant and dielectric loss tangent may tend to increase due to an increase in the number of highly polar ends in the polyimide molecular chain. If the weight-average molecular weight is more than 60,000, the molecular chain length becomes longer and it becomes difficult to form an ordered structure, so that the dielectric constant and dielectric loss tangent may tend to increase.
[0049] Condition f) The following formula (i): CM value = (C / Mw) x 10 4 (i) [In the formula, C represents the weight content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide, and Mw represents the weight average molecular weight of the polyimide.] The CM value, which is an index showing the amount of six-membered aromatic rings contained in the polyimide, is within the range of 3 to 38, as calculated based on the above. Setting the CM value within an appropriate range is effective in lowering the dielectric tangent of polyimide, and when the CM value is less than 3, the aromatic ring concentration is low, which increases molecular mobility and increases the dielectric tangent. On the other hand, when the CM value exceeds 38, the aromatic ring concentration becomes excessive, which causes high polarization and increases the dielectric tangent.
[0050] Condition g) The weight content of carbon atoms derived from 6-membered aromatic rings (excluding carbon atoms of 6-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in all diamine components of the raw materials is in the range of more than 0 and 32% by weight or less. By controlling the content of aromatic rings in the adhesive polyimide within an appropriate range, the interaction between the aromatic rings in the polyimide limits the molecular motion, and the effect of lowering the dielectric tangent is realized. For this purpose, it is effective to set the content of carbon atoms derived from 6-membered aromatic rings to the total content of carbon atoms in the diamine component of the raw material within the above range. If the content of carbon atoms derived from 6-membered aromatic rings to the total content of all atoms in all diamine components of the raw material exceeds 32% by weight, the polarity of the resulting polyimide molecule becomes large, and the dielectric tangent becomes high.
[0051] Condition h) The following formula (ii): DM value = (D / Mw) x 10 4 (ii) [In the formula, D represents the weight content of carbon atoms derived from 6-membered aromatic rings (excluding carbon atoms of 6-membered aromatic rings derived from the dimer diamine composition) relative to the total content of all atoms in all diamine residues, and Mw represents the weight average molecular weight of the polyimide.] The DM value, which is an index showing the amount of six-membered aromatic rings derived from the diamine component contained in the polyimide, calculated based on the above, is in the range of more than 0 and 32 or less. For the same reason as in condition g, it is effective to set the content of carbon atoms derived from six-membered aromatic rings in the diamine residue relative to the total content of all atoms in the polyimide within the above range.
[0052] Next, the acid anhydride residue and the diamine residue constituting the adhesive polyimide will be described. As described above, the adhesive polyimide contains a fluorine-containing tetracarboxylic acid residue and / or a fluorine-containing diamine residue, and may further contain other tetracarboxylic acid residues and / or diamine residues. Hereinafter, the tetracarboxylic acid residues other than the fluorine-containing tetracarboxylic acid residues and the diamine residues other than the fluorine-containing diamine residues will be described.
[0053] (acid anhydride) The adhesive polyimide may be made of any tetracarboxylic anhydride generally used in thermoplastic polyimides as a raw material, without any particular limitations. However, it is preferable to use a raw material containing 50 mol % or more of tetracarboxylic anhydrides represented by the following general formula (1) and / or (2) in total relative to the total tetracarboxylic anhydride components. In other words, the adhesive polyimide preferably contains 50 mol % or more of tetracarboxylic acid residues derived from tetracarboxylic anhydrides represented by the following general formula (1) and / or (2) in total relative to the total tetracarboxylic acid residues. By containing 90 mol % or more of tetracarboxylic acid residues derived from tetracarboxylic anhydrides represented by the following general formula (1) and / or (2) in total relative to the total tetracarboxylic acid residues, it is preferable that the adhesive polyimide is easily compatible with flexibility and heat resistance. If the total amount of tetracarboxylic acid residues derived from tetracarboxylic anhydrides represented by the following general formula (1) and / or (2) is less than 50 mol %, the adhesive polyimide tends to have a low solvent solubility.
[0054] [ka]
[0055] In general formula (1), X represents a single bond or a divalent group selected from the following formulas, and in general formula (2), the cyclic moiety represented by Y represents the formation of a cyclic saturated hydrocarbon group selected from a 4-membered ring, a 5-membered ring, a 6-membered ring, a 7-membered ring, or an 8-membered ring.
[0056] [ka]
[0057] In the above formula, Z represents -C6H4-, -(CH2)n-, or -CH2-CH(-OC(=O)-CH3)-CH2-, where n represents an integer of 1 to 20.
[0058] Examples of the tetracarboxylic anhydride represented by the above general formula (1) include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic monoester acid anhydride) (TAHQ), and ethylene glycol bisanhydrotrimellitate (TMEG). Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is particularly preferred. When BTDA is used, the carbonyl group (ketone group) contributes to adhesion, so that the adhesion of the adhesive polyimide can be improved. In addition, ketone groups present in the molecular skeleton of BTDA may react with amino groups of an amino compound for crosslinking (described below) to form C=N bonds, which may facilitate the development of an effect of improving heat resistance. From this viewpoint, it is preferable that the tetracarboxylic acid residues derived from BTDA be contained in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, of all tetracarboxylic acid residues.
[0059] Examples of the tetracarboxylic acid anhydride represented by the general formula (2) include 1,2,3,4-cyclobutane tetracarboxylic acid dianhydride, 1,2,3,4-cyclopentane tetracarboxylic acid dianhydride, 1,2,4,5-cyclohexane tetracarboxylic acid dianhydride, 1,2,4,5-cycloheptane tetracarboxylic acid dianhydride, and 1,2,5,6-cyclooctane tetracarboxylic acid dianhydride.
[0060] The adhesive polyimide may contain a tetracarboxylic acid residue derived from an acid anhydride other than the tetracarboxylic acid anhydrides represented by the above general formula (1) and general formula (2) within the scope of the invention. Such a tetracarboxylic acid residue is not particularly limited, and examples thereof include pyromellitic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'- or 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, and the like. carboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 1, 2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetra Examples of the tetracarboxylic acid residues include tetracarboxylic acid residues derived from aromatic tetracarboxylic acid dianhydrides such as carboxylic acid dianhydrides, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic acid dianhydride, pyrazine-2,3,5,6-tetracarboxylic acid dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic acid dianhydride, thiophene-2,3,4,5-tetracarboxylic acid dianhydride, and 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride.
[0061] (Diamine) The adhesive polyimide may be made of any diamine compound generally used in thermoplastic polyimides as a raw material without any particular restrictions, but a raw material containing 40 mol% or more of aliphatic diamines relative to the total diamine components is used. In other words, as per the above condition b, the adhesive polyimide contains 40 mol% or more of diamine residues derived from aliphatic diamines relative to the total diamine residues. As the aliphatic diamine, it is preferable to use a dimer diamine composition mainly composed of a dimer diamine in which two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups.
[0062] The dimer diamine composition is a refined product containing the following component (a) as a main component with the amounts of components (b) and (c) being controlled.
[0063] (a) dimer diamine; The dimer diamine of the component (a) means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid, linoleic acid, and linolenic acid, but contains any amount of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In addition, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid. The dimer diamine of component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having 18 to 54 carbon atoms, preferably 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group.
[0064] As a feature of dimer diamine, it is possible to impart characteristics derived from the skeleton of dimer acid. That is, since dimer diamine is an aliphatic macromolecule with a molecular weight of about 560 to 620, it is possible to increase the molar volume of the molecule and relatively reduce the polar group of the polyimide. It is considered that such a feature of dimer acid type diamine contributes to improving the dielectric properties by reducing the relative dielectric constant and dielectric loss tangent while suppressing the deterioration of the heat resistance of the polyimide. In addition, since it has two freely moving hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, it is not only possible to impart flexibility to the polyimide, but also possible to make the polyimide have an asymmetric chemical structure or a non-planar chemical structure, and therefore it is considered that it is possible to reduce the dielectric constant of the polyimide.
[0065] The dimer diamine composition is preferably one in which the dimer diamine content of the (a) component is increased to 96% by weight or more, preferably 97% by weight or more, more preferably 98% by weight or more by a purification method such as molecular distillation. By making the dimer diamine content of the (a) component 96% by weight or more, the spread of the molecular weight distribution of the polyimide can be suppressed. If technically possible, it is best that all (100% by weight) of the dimer diamine composition is composed of the dimer diamine of the (a) component. The dimer diamine composition may contain a dimer diamine having a 6-membered aromatic ring as a molecular skeleton. In the polyimide of the present embodiment, attention is paid to and the ratio of aromatic monomers directly bonded to the imide bond site is the object of control, but in the dimer diamine having a 6-membered aromatic ring, the 6-membered aromatic ring is an imide bond via an aliphatic chain having a length of 7 carbon atoms or more, so the 6-membered aromatic ring in the polyimide of the present embodiment is not the object of control. Therefore, the 6-membered aromatic ring derived from the dimer diamine is excluded from the conditions d, f, g, and h in the adhesive polyimide. The proportion of aromatic rings derived from dimer diamine is preferably 20 mol % or less per mol of amino groups, as quantified by 1H-NMR.
[0066] (b) a monoamine compound obtained by substituting a terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group; The monobasic acid compound having 10 to 40 carbon atoms is a mixture of a monobasic unsaturated fatty acid having 10 to 20 carbon atoms derived from the raw material of dimer acid, and a monobasic acid compound having 21 to 40 carbon atoms which is a by-product during the production of dimer acid. The monoamine compound is obtained by substituting the terminal carboxylic acid group of these monobasic acid compounds with a primary aminomethyl group or an amino group.
[0067] The monoamine compound (b) is a component that suppresses an increase in the molecular weight of the polyimide. During polymerization of the polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal acid anhydride group of the polyamic acid or polyimide to cap the terminal acid anhydride group, thereby suppressing an increase in the molecular weight of the polyamic acid or polyimide.
[0068] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine); The polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms is a polybasic acid compound mainly composed of a tribasic acid compound having 41 to 80 carbon atoms, which is a by-product during the production of dimer acid. It may also contain a polymerized fatty acid other than dimer acid having 41 to 80 carbon atoms. The amine compound is obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.
[0069] The amine compound (c) is a component that promotes an increase in the molecular weight of the polyimide. The trifunctional or higher amino group, the main component of which is a triamine derived from a trimer acid, reacts with the terminal acid anhydride group of the polyamic acid or polyimide, rapidly increasing the molecular weight of the polyimide. In addition, amine compounds derived from polymerized fatty acids other than dimer acids having 41 to 80 carbon atoms also increase the molecular weight of the polyimide, causing gelation of the polyamic acid or polyimide.
[0070] When each component is quantified by measurement using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top, and peak end of each component of the dimer diamine composition, a sample of the dimer diamine composition treated with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard. Using the sample thus prepared, each component is quantified by the area percentage of the GPC chromatogram. The peak start and peak end of each component are the minimum values of each peak curve, and the area percentage of the chromatogram can be calculated based on this.
[0071] In addition, the dimer diamine composition has a total area percentage of components (b) and (c) of 4% or less, preferably less than 4%, in a chromatogram obtained by GPC measurement. By keeping the total area percentage of components (b) and (c) at 4% or less, the broadening of the molecular weight distribution of the polyimide can be suppressed.
[0072] The area percentage of the chromatogram of the (b) component is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it in such a range, it is possible to suppress the decrease in the molecular weight of the polyimide, and further to widen the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component. It is not necessary for the (b) component to be contained in the dimer diamine composition.
[0073] The area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it in such a range, a sudden increase in the molecular weight of the polyimide can be suppressed, and further, an increase in the dielectric tangent of the resin film over a wide frequency range can be suppressed. Note that component (c) does not have to be contained in the dimer diamine composition.
[0074] In addition, when the ratio (b / c) of the area percentages of the chromatograms of the components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and less than 1.0. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0075] Furthermore, when the ratio (b / c) of the area percentages of the components (b) and (c) in the chromatograms is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably 0.97 or more and 1.1 or less. By setting such a molar ratio, it becomes easier to control the molecular weight of the polyimide.
[0076] The dimer diamine composition is available as a commercially available product, and is preferably purified to reduce the amount of components other than the dimer diamine of the component (a), for example, it is preferable to make the component (a) 96% by weight or more. The purification method is not particularly limited, but known methods such as distillation and precipitation purification are suitable. Examples of commercially available dimer diamine compositions include PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan.
[0077] The adhesive polyimide may contain a diamine residue derived from a diamine component other than the above. As such a diamine residue, for example, bisanilinefluorene (BAFL), 9,9-bis(3-methyl-4-aminophenyl)fluorene, 9,9-bis[4-(aminophenoxy)phenyl]fluorene, or a diamine residue derived from a diamine compound represented by general formula (B1) to (B7) is preferable. In particular, a diamine having a fluorene skeleton, such as BAFL, contains four aromatic rings, and can be advantageously used for the purpose of adjusting the aromatic ring concentration.
[0078] [ka]
[0079] In formulas (B1) to (B7), R1 independently represents a monovalent hydrocarbon group or alkoxy group having 1 to 6 carbon atoms, linking group A independently represents a divalent group selected from -O-, -S-, -CO-, -SO-, -SO2-, -COO-, -CH2-, -C(CH3)2-, -NH-, or -CONH-, and n1 independently represents an integer of 0 to 4. However, formula (B3) excluding those that overlap with formula (B2), and formula (B5) excluding those that overlap with formula (B4). Here, "independently" means that in one or more of the above formulas (B1) to (B7), multiple linking groups A, multiple R1s, or multiple n1s may be the same or different. In the above formulas (B1) to (B7), the hydrogen atoms in the two terminal amino groups may be substituted, for example, -NR2R3 (wherein R2 and R3 independently represent any substituent such as an alkyl group).
[0080] The diamine represented by formula (B1) (hereinafter, sometimes referred to as "diamine (B1)") is an aromatic diamine having two benzene rings. In this diamine (B1), since at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, the degree of freedom of the polyimide molecular chain is increased, resulting in high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B1), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -CO-, -SO2-, or -S-.
[0081] Examples of the diamine (B1) include 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, and (3,3'-bisamino)diphenylamine.
[0082] The diamine represented by formula (B2) (hereinafter sometimes referred to as "diamine (B2)") is an aromatic diamine having three benzene rings. In this diamine (B2), the amino group directly bonded to at least one benzene ring and the divalent linking group A are at the meta position, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is thought to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B2), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-.
[0083] Examples of the diamine (B2) include 1,4-bis(3-aminophenoxy)benzene, 3-[4-(4-aminophenoxy)phenoxy]benzeneamine, and 3-[3-(4-aminophenoxy)phenoxy]benzeneamine.
[0084] The diamine represented by formula (B3) (hereinafter, sometimes referred to as "diamine (B3)") is an aromatic diamine having three benzene rings. In this diamine (B3), two divalent linking groups A directly bonded to one benzene ring are in meta positions with respect to each other, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B3), the thermoplasticity of the polyimide is increased. Here, as the linking group A, -O- is preferable.
[0085] Examples of diamine (B3) include 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene)bisoxy]bisaniline, 4,4'-[4-methyl-(1,3-phenylene)bisoxy]bisaniline, and 4,4'-[5-methyl-(1,3-phenylene)bisoxy]bisaniline.
[0086] The diamine represented by formula (B4) (hereinafter, sometimes referred to as "diamine (B4)") is an aromatic diamine having four benzene rings. This diamine (B4) has high flexibility because at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B4) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -SO2-, -CO-, or -CONH-.
[0087] Examples of the diamine (B4) include bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]benzophenone, and bis[4,4'-(3-aminophenoxy)]benzanilide.
[0088] The diamine represented by formula (B5) (hereinafter sometimes referred to as "diamine (B5)") is an aromatic diamine having four benzene rings. In this diamine (B5), two divalent linking groups A directly bonded to at least one benzene ring are mutually at meta positions, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B5), the thermoplasticity of the polyimide is increased. Here, as the linking group A, -O- is preferable.
[0089] Examples of the diamine (B5) include 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4'-[oxybis(3,1-phenyleneoxy)]bisaniline, and the like.
[0090] The diamine represented by formula (B6) (hereinafter sometimes referred to as "diamine (B6)") is an aromatic diamine having four benzene rings. This diamine (B6) has high flexibility due to having at least two ether bonds, and is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B6) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -C(CH3)2-, -O-, -SO2-, or -CO-.
[0091] Examples of diamines (B6) include 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), and bis[4-(4-aminophenoxy)phenyl]ketone (BAPK).
[0092] The diamine represented by formula (B7) (hereinafter sometimes referred to as "diamine (B7)") is an aromatic diamine having four benzene rings. This diamine (B7) has a highly flexible divalent linking group A on both sides of the diphenyl skeleton, which is believed to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B7) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-.
[0093] Examples of the diamine (B7) include bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, and the like.
[0094] The adhesive polyimide preferably contains diamine residues derived from at least one diamine compound selected from diamines (B1) to (B7) in an amount of 1 mol % to 40 mol %, more preferably 5 mol % to 35 mol %, based on the total diamine residues. Since diamines (B1) to (B7) have flexible molecular structures, the use of at least one diamine compound selected from these in an amount within the above range can improve the flexibility of the polyimide molecular chain and impart thermoplasticity.
[0095] The adhesive polyimide may further contain diamine residues other than those mentioned above, provided that the effect of the invention is not impaired.
[0096] The adhesive polyimide can be produced by reacting the above-mentioned acid anhydride component and diamine component in a solvent, generating polyamic acid, and then heating to close the ring. For example, the acid anhydride component and diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such an organic solvent is not particularly limited, but it is preferable to adjust the amount so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.
[0097] The synthesized polyamic acid is usually advantageously used as a solution in a reaction solvent, but it can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is also advantageously used because it generally has excellent solubility in solvents. The viscosity of the polyamic acid solution is preferably within the range of 500 mPa·s to 100,000 mPa·s. If it is outside this range, defects such as uneven thickness and streaks are likely to occur in the film during coating using a coater or the like.
[0098] The method for imidizing polyamic acid to form polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated in the above-mentioned solvent at a temperature in the range of 80 to 400° C. for 1 to 24 hours is preferably used. The temperature may be constant, or the temperature may be changed during the process.
[0099] In the adhesive polyimide, by selecting the types of the acid anhydride component and the diamine component, or by selecting the molar ratio of each when two or more types of acid anhydride components or diamine components are used, it is possible to control physical properties such as dielectric properties, thermal expansion coefficient, tensile modulus, glass transition temperature, etc. When the adhesive polyimide has a plurality of structural units, they may be present as blocks or randomly, but are preferably present randomly.
[0100] The imide group concentration of the adhesive polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to the increase in polar groups, and Tg and elastic modulus increase.
[0101] The adhesive polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.
[0102] The adhesive polyimide can be made into an adhesive composition by appropriately blending optional components such as a plasticizer, other curable resin components such as an epoxy resin, a curing agent, a curing accelerator, an organic filler, an inorganic filler, a coupling agent, a solvent, and a flame retardant.
[0103] (Crosslinking of adhesive polyimide) When the adhesive polyimide has a ketone group, the ketone group can be reacted with an amino group of an amino compound having at least two primary amino groups as functional groups (hereinafter, sometimes referred to as "amino compound for crosslinking") to form a C=N bond, thereby forming a crosslinked structure. A polyimide having such a crosslinked structure (hereinafter, sometimes referred to as "crosslinked polyimide") is an application example of an adhesive polyimide and is a preferred embodiment. Since the weight average molecular weight varies greatly due to crosslinking, it is sufficient that the adhesive polyimide before crosslinking satisfies conditions a to c and, if necessary, conditions d to h, and the crosslinked polyimide does not have to satisfy these conditions. In addition, an adhesive composition in which a crosslinking agent is blended with an adhesive polyimide having a ketone group is another application example of an adhesive polyimide and is a preferred embodiment. The heat resistance of the adhesive polyimide can be improved by forming a crosslinked structure. A preferred example of a tetracarboxylic acid anhydride for forming an adhesive polyimide having a ketone group is 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a preferred example of a diamine compound is an aromatic diamine such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) or 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB).
[0104] For the purpose of forming a crosslinked structure, it is particularly preferred to react a crosslinking amino compound with the above adhesive polyimide containing BTDA residues derived from BTDA in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, based on the total tetracarboxylic acid residues. In the present invention, the term "BTDA residue" refers to a tetravalent group derived from BTDA.
[0105] Examples of the amino compound for forming a crosslink include (I) a dihydrazide compound, (II) an aromatic diamine, and (III) an aliphatic amine. Among these, a dihydrazide compound is preferred. Aliphatic amines other than dihydrazide compounds are likely to form a crosslinked structure even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form a crosslinked structure. In this way, when a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of the dihydrazide compound include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl ester dihydrazide, ... Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoedioic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.
[0106] In addition, the above amino compounds, such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines, can also be used in combination of two or more kinds beyond categories, such as a combination of (I) and (II), a combination of (I) and (III), or a combination of (I), (II) and (III).
[0107] In addition, from the viewpoint of making the network structure formed by the crosslinking by the crosslinking amino compound denser, the crosslinking amino compound used in the present invention preferably has a molecular weight (weight average molecular weight when the crosslinking amino compound is an oligomer) of 5,000 or less, more preferably 90 to 2,000, and even more preferably 100 to 1,500. Among these, crosslinking amino compounds having a molecular weight of 100 to 1,000 are particularly preferred. When the molecular weight of the crosslinking amino compound is less than 90, only one amino group of the crosslinking amino compound forms a C=N bond with a ketone group of the adhesive polyimide, and the periphery of the remaining amino group becomes three-dimensionally bulky, so that the remaining amino group tends to have difficulty in forming a C=N bond.
[0108] When crosslinking the ketone group in the adhesive polyimide with the crosslinking amino compound, the crosslinking amino compound is added to a resin solution containing the adhesive polyimide to cause a condensation reaction between the ketone group in the adhesive polyimide and the primary amino group of the crosslinking amino compound. This condensation reaction causes the resin solution to harden into a hardened product. In this case, the amount of the crosslinking amino compound added can be 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol of primary amino group per 1 mol of ketone group. When the amount of crosslinking amino compound added is such that the total number of primary amino groups per mole of ketone groups is less than 0.004 moles, crosslinking by the crosslinking amino compound is insufficient, and heat resistance after curing tends to be difficult to exhibit. When the amount of crosslinking amino compound added exceeds 1.5 moles, unreacted crosslinking amino compound acts as a thermoplasticizer, tending to reduce the heat resistance of the adhesive layer.
[0109] The conditions of the condensation reaction for forming crosslinks are not particularly limited as long as the ketone group in the adhesive polyimide reacts with the primary amino group of the amino compound for forming crosslinks to form an imine bond (C=N bond). The temperature of the heat condensation is preferably within the range of, for example, 120 to 220°C, more preferably within the range of 140 to 200°C, for the purpose of releasing water produced by condensation to the outside of the system, or for the purpose of simplifying the condensation step when the heat condensation reaction is carried out subsequently to the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm. -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.
[0110] The thermal condensation of the ketone group of the adhesive polyimide with the primary amino group of the crosslinking amino compound can be carried out, for example, by the following method: (1) A method in which, following the synthesis (imidization) of adhesive polyimide, an amino compound for crosslinking is added and heated; (2) A method in which an excess amount of an amino compound is charged in advance as a diamine component, and following the synthesis (imidization) of an adhesive polyimide, the remaining amino compound that is not involved in imidization or amidation is used as an amino compound for crosslinking and heated together with the adhesive polyimide; Or, (3) A method in which the adhesive polyimide solution (adhesive composition) containing the above-mentioned amino compound for crosslinking is processed into a predetermined shape (for example, after being applied to a substrate or formed into a film), and then heated; This can be done by, etc.
[0111] In the above description, an example of a crosslinked polyimide having a crosslinked structure formed by the formation of an imine bond has been given in order to impart heat resistance to the adhesive polyimide. However, the present invention is not limited to this example. As a method for curing the polyimide, it is also possible to mix and cure the polyimide with a compound having an unsaturated bond, such as an epoxy resin, an epoxy resin curing agent, maleimide, an activated ester resin, or a resin having a styrene skeleton.
[0112] [Adhesive composition] Since the adhesive polyimide is soluble in a solvent, it can be used in the form of an adhesive composition (polyimide solution) containing a solvent. That is, the adhesive composition contains an adhesive polyimide and a solvent capable of dissolving the adhesive polyimide. The adhesive composition can also contain an amino compound for crosslinking as an optional component. The adhesive composition contains an adhesive polyimide as the main component of the resin component, preferably 70% by weight or more of the resin component, more preferably 90% by weight or more of the resin component, and most preferably the entire resin component. The main component of the resin component means a component that is contained in an amount of 50% by weight or more of the total resin component.
[0113] The solvent is not particularly limited as long as it can dissolve the adhesive polyimide, and examples thereof include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diglyme, triglyme, methanol, ethanol, benzyl alcohol, cresol, acetone, etc. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination.
[0114] In the adhesive composition, the blending ratio of the adhesive polyimide and the solvent is not particularly limited as long as the viscosity of the composition can be maintained at a level that allows coating. The viscosity of the adhesive composition is preferably within a range of, for example, 500 mPa·s to 100,000 mPa·s. If the viscosity is outside this range, defects such as uneven thickness and streaks are likely to occur in the resin film during coating.
[0115] The adhesive composition may contain, as appropriate, optional components, such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic fillers, inorganic fillers, coupling agents, solvents, and flame retardants, provided the effects of the invention are not impaired.
[0116] [Polyimide film / adhesive film] The polyimide film according to one embodiment of the present invention is obtained by processing the above-mentioned adhesive polyimide or crosslinked polyimide into a film shape. The polyimide film contains fluorine-containing tetracarboxylic acid residues and / or fluorine-containing diamine residues, and the total content of fluorine atoms is within the range of 1% by weight to 20% by weight based on the total content of all atoms in the polyimide.
[0117] The polyimide film preferably has a dielectric loss tangent (Tan δ) of less than 0.002 and a relative dielectric constant (ε) of 3.0 or less at 10 GHz measured by a split post dielectric resonator (SPDR) after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23°C and 50% RH. If the dielectric loss tangent (Tan δ) and the relative dielectric constant (ε) exceed the above values, this leads to an increase in dielectric loss when applied to a circuit board, and is likely to cause inconveniences such as loss of electrical signals on the transmission path of high-frequency signals.
[0118] A preferred form of the polyimide film is an adhesive film. The adhesive film is not particularly limited as long as it is a film containing the adhesive polyimide or crosslinked polyimide as the main component of the resin component, preferably 70% by weight or more of the resin component, more preferably 90% by weight or more of the resin component, and most preferably the entire resin component. The main component of the resin component means a component that is contained in an amount of 50% by weight or more of the total resin component. The adhesive film may be a film (sheet) made of adhesive polyimide or crosslinked polyimide, or may be laminated on a resin base material such as an inorganic material such as copper foil or glass plate, or a polyimide film, polyamide film, or polyester film. The adhesive film may be appropriately blended with optional components such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic fillers, inorganic fillers, coupling agents, and flame retardants.
[0119] The tensile modulus of the adhesive film is preferably 3000 MPa or less, more preferably 100 MPa to 2500 MPa, and more preferably 200 MPa to 2000 MPa. If the tensile modulus is less than 100 MPa, the film is likely to wrinkle, and handling may be impaired due to air entrapment during lamination. If the tensile modulus exceeds 3000 MPa, the film may not adhere to the substrate. Agent When films are laminated, warping may occur and dimensional stability may decrease. By setting the tensile modulus within the above range, it is possible to obtain a laminate that has good handleability, suppresses warping, and has excellent dimensional stability.
[0120] The method for producing the adhesive film of the present embodiment is not particularly limited, but the following methods [1] to [3] can be exemplified. [1] A method in which an adhesive polyimide is applied in a solution state (e.g., in the form of an adhesive composition) to any substrate to form a coating film, which is then dried at a temperature of, for example, 80 to 180°C to form a film, and then peeled off from the substrate as necessary. [2] A method in which a solution of polyamic acid, which is a precursor of adhesive polyimide, is applied to any substrate, dried, and then imidized to form a film, which is then peeled off from the substrate as necessary. [3] A method in which a solution of polyamic acid, a precursor of adhesive polyimide, is applied to any substrate and dried, and then the polyamic acid gel film is peeled off from the substrate and imidized to produce an adhesive film. The method for applying the adhesive polyimide solution (or polyamic acid solution) onto the substrate is not particularly limited, and it is possible to apply it using, for example, a coater such as a comma, die, knife or lip coater.
[0121] Next, specific examples of laminates, metal-clad laminates, circuit boards, and multilayer circuit boards, which are preferred embodiments to which a resin film is applied, will be described.
[0122] [Laminate] As shown in FIG. 1, the laminate 100 according to an embodiment of the present invention has a substrate 10 and an adhesive layer 20 laminated on at least one surface of the substrate 10, and the adhesive layer 20 is made of the adhesive film. The laminate 100 may include any layer other than the above. Examples of the substrate 10 in the laminate 100 include substrates made of inorganic materials such as copper foil and glass plate, and substrates made of resin materials such as polyimide films, polyamide films, and polyester films. The laminate 100 can be manufactured according to any one of the methods [1] to [3] for manufacturing the adhesive film, except that the laminate 100 is not peeled off from the substrate 10. The laminate 100 may also be manufactured by preparing the substrate 10 and the adhesive film separately and bonding them together. Preferred embodiments of the laminate 100 include a coverlay film, a copper foil with resin, and the like.
[0123] [Coverlay film] Although not shown, the coverlay film, which is one embodiment of the laminate 100, has a coverlay film material layer as a substrate 10 and an adhesive layer 20 laminated on one side of the coverlay film material layer, the adhesive layer 20 being made of the adhesive film. The coverlay film may include any layer other than those described above.
[0124] The material of the coverlay film material layer is not particularly limited, but for example, polyimide-based films such as polyimide resins, polyetherimide resins, and polyamideimide resins, polyamide-based films, and polyester-based films can be used. Among these, it is preferable to use polyimide-based films with excellent heat resistance. In addition, the coverlay film material can contain a black pigment in order to effectively exhibit light-shielding properties, concealing properties, design properties, and the like, and can also contain optional components such as matte pigments that suppress the gloss of the surface, within a range that does not impair the effect of improving the dielectric properties.
[0125] The thickness of the coverlay film material layer is not particularly limited, but is preferably within the range of, for example, 5 μm or more and 100 μm or less. The thickness of the adhesive layer 20 is not particularly limited, but is preferably within the range of, for example, 10 μm or more and 75 μm or less.
[0126] The coverlay film of the present embodiment can be produced by the method exemplified below. First, as a first method, polyimide that will become the adhesive layer 20 is applied in a solution state (for example, a varnish state containing a solvent is preferable, and an adhesive composition is preferable) to one side of a film material layer for the coverlay, and then the polyimide is dried at a temperature of, for example, 80 to 180°C to form the adhesive layer 20, thereby forming a coverlay film having a film material layer for the coverlay and the adhesive layer 20.
[0127] As a second method, polyimide for adhesive layer 20 can be applied in a solution state (for example, a varnish state containing a solvent, preferably an adhesive composition) onto any substrate, dried at a temperature of, for example, 80 to 180°C, and then peeled off to form a resin film for adhesive layer 20, and this resin film can be thermocompressed with a film material layer for the coverlay at a temperature of, for example, 60 to 220°C to form a coverlay film.
[0128] [Copper foil with resin] Although not shown, a resin-coated copper foil, which is another embodiment of the laminate 100, is obtained by laminating an adhesive layer 20 on at least one side of a copper foil as a substrate 10, and the adhesive layer 20 is made of the above-mentioned adhesive film. The resin-coated copper foil of this embodiment may include any layer other than those described above.
[0129] The thickness of the adhesive layer 20 in the resin-coated copper foil is preferably within the range of 0.1 to 125 μm, and more preferably within the range of 0.3 to 100 μm. If the thickness of the adhesive layer 20 is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer 20 exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of lowering the dielectric constant and the dielectric loss tangent, the thickness of the adhesive layer 20 is preferably 3 μm or more.
[0130] The material of the copper foil in the resin-coated copper foil is preferably one mainly composed of copper or a copper alloy. The thickness of the copper foil is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the copper foil is preferably 5 μm. The copper foil may be a rolled copper foil or an electrolytic copper foil. In addition, a commercially available copper foil can be used as the copper foil.
[0131] The resin-attached copper foil may be prepared, for example, by sputtering a metal onto an adhesive film to form a seed layer, and then forming a copper layer, for example, by copper plating, or by laminating an adhesive film and a copper foil by a method such as thermocompression bonding. Furthermore, the resin-attached copper foil may be prepared by casting a coating solution of an adhesive polyimide or a precursor thereof onto the copper foil, drying the coating film to form an adhesive layer 20, and then carrying out the necessary heat treatment.
[0132] [Metal-clad laminate] (First aspect) The metal-clad laminate according to one embodiment of the present invention includes an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, at least one of the insulating resin layers being made of the adhesive film. Note that the metal-clad laminate according to this embodiment may include any layer other than those described above.
[0133] (Second aspect) A metal-clad laminate according to another embodiment of the present invention is a so-called three-layer metal-clad laminate 101 including an insulating resin layer 30, an adhesive layer 20 laminated on at least one surface of the insulating resin layer 30, and a metal layer M laminated on the insulating resin layer 30 via the adhesive layer 20, as shown in FIG. 2, and the adhesive layer 20 is made of the above-mentioned adhesive film. The three-layer metal-clad laminate 101 may include any layer other than the above. The three-layer metal-clad laminate 101 may have the adhesive layer 20 on one or both surfaces of the insulating resin layer 30, and the metal layer M may have the adhesive layer 20 on one or both surfaces of the insulating resin layer 30. In other words, the three-layer metal-clad laminate 101 may be a single-sided metal-clad laminate or a double-sided metal-clad laminate. A single-sided or double-sided FPC can be manufactured by performing wiring circuit processing such as etching the metal layer M of the three-layer metal-clad laminate 101.
[0134] The insulating resin layer 30 in the three-layer metal-clad laminate 101 is not particularly limited as long as it is made of a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ETFE, etc., but is preferably made of polyimide. The polyimide layer constituting the insulating resin layer 30 may be a single layer or multiple layers, but preferably includes a non-thermoplastic polyimide layer.
[0135] The thickness of the insulating resin layer 30 in the three-layer metal-clad laminate 101 is preferably within a range of, for example, 1 to 125 μm, and more preferably within a range of 5 to 100 μm. If the thickness of the insulating resin layer 30 is less than the above lower limit, problems such as inability to ensure sufficient electrical insulation may occur. On the other hand, if the thickness of the insulating resin layer 30 exceeds the above upper limit, problems such as the metal-clad laminate being more likely to warp may occur.
[0136] The thickness of the adhesive layer 20 in the three-layer metal-clad laminate 101 is preferably within a range of, for example, 0.1 to 125 μm, and more preferably within a range of 0.3 to 100 μm. In the three-layer metal-clad laminate 101 of the present embodiment, if the thickness of the adhesive layer 20 is less than the above lower limit, problems such as insufficient adhesion may occur. On the other hand, if the thickness of the adhesive layer 20 exceeds the above upper limit, problems such as reduced dimensional stability may occur. In addition, from the viewpoint of reducing the dielectric constant and dielectric loss tangent of the entire insulating layer, which is a laminate of the insulating resin layer 30 and the adhesive layer 20, the thickness of the adhesive layer 20 is preferably 3 μm or more.
[0137] Moreover, the ratio of the thickness of the insulating resin layer 30 to the thickness of the adhesive layer 20 (thickness of the insulating resin layer 30 / thickness of the adhesive layer 20) is preferably within a range of, for example, 0.1 to 3.0, and more preferably within a range of 0.15 to 2.0. By setting such a ratio, it is possible to suppress warping of the three-layer metal-clad laminate 101. Moreover, the insulating resin layer 30 may contain a filler as necessary. Examples of the filler include silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, and metal salts of organic phosphinic acid. These can be used alone or in combination of two or more kinds.
[0138] (Third aspect) A metal-clad laminate according to still another embodiment of the present invention is, for example, as shown in Fig. 3, a laminated type metal-clad laminate 102 formed by laminating at least two single-sided metal-clad laminates via an adhesive layer 20. The laminated type metal-clad laminate 102 comprises a first single-sided metal-clad laminate 41, a second single-sided metal-clad laminate 42, and an adhesive layer 20 laminated between the first single-sided metal-clad laminate 41 and the second single-sided metal-clad laminate 42, and the adhesive layer 20 is made of the above-mentioned adhesive film. Here, the first single-sided metal-clad laminate 41 has a first metal layer M1 and a first insulating resin layer 31 laminated on at least one side of the first metal layer M1. The second single-sided metal-clad laminate 42 has a second metal layer M2 and a second insulating resin layer 32 laminated on at least one side of the second metal layer M2. The adhesive layer 20 is disposed so as to abut against the first insulating resin layer 31 and the second insulating resin layer 32. The laminated metal-clad laminate 102 may include any layer other than those described above.
[0139] The first insulating resin layer 31 and the second insulating resin layer 32 in the laminated metal-clad laminate 102 may have the same configuration as the insulating resin layer 30 in the three-layer metal-clad laminate 101 of the second embodiment. The laminated metal-clad laminate 102 can be manufactured by preparing a first single-sided metal-clad laminate 41 and a second single-sided metal-clad laminate 42, and placing an adhesive film between the first insulating resin layer 31 and the second insulating resin layer 32 and laminating them together.
[0140] (Fourth aspect) 4, a metal-clad laminate according to still another embodiment of the present invention is a single-sided metal-clad laminate 103 with an adhesive layer, which includes a single-sided metal-clad laminate having an insulating resin layer 33 and a metal layer M laminated on one side of the insulating resin layer 33, and an adhesive layer 20 laminated on the other side of the insulating resin layer 33, and the adhesive layer 20 is made of the above-mentioned adhesive film. Note that the metal-clad laminate 103 with an adhesive layer may include any layer other than those described above. The insulating resin layer 33 in the adhesive layer-attached metal-clad laminate 103 may have a configuration similar to that of the insulating resin layer 30 in the three-layer metal-clad laminate 101 of the second embodiment. The adhesive layer-attached metal-clad laminate 103 can be manufactured by preparing a single-sided metal-clad laminate having an insulating resin layer 33 and a metal layer M, and laminating an adhesive film to the insulating resin layer 33 side.
[0141] In the metal-clad laminate of any of the first to fourth exemplary embodiments above, the material of the metal layer M (including the first metal layer M1 and the second metal layer M2, the same applies below) is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferred. The material of the wiring layer in the circuit board described below is also the same as that of the metal layer M.
[0142] The thickness of the metal layer M is not particularly limited, but when a metal foil such as copper foil is used, it is preferably 35 μm or less, more preferably in the range of 5 to 25 μm. From the viewpoint of production stability and handling, the lower limit of the thickness of the metal foil is preferably 5 μm. When copper foil is used, it may be rolled copper foil or electrolytic copper foil. In addition, commercially available copper foil may be used as the copper foil. In addition, the metal foil may be subjected to a surface treatment such as siding, aluminum alcoholate, aluminum chelate, silane coupling agent, etc., for the purpose of, for example, rust prevention treatment or improvement of adhesive strength.
[0143] [Circuit board] (First aspect) The circuit board according to the embodiment of the present invention is obtained by wiring the metal layer of the metal-clad laminate according to any of the above embodiments. One or more metal layers of the metal-clad laminate are patterned by a conventional method to form a wiring layer (conductor circuit layer), thereby manufacturing a circuit board such as an FPC. The circuit board may include a coverlay film that covers the wiring layer.
[0144] (Second aspect) 5, a circuit board 200 according to another embodiment of the present invention includes a first base material 11, a wiring layer 50 laminated on at least one surface of the first base material 11, and an adhesive layer 20 laminated on the surface of the first base material 11 facing the wiring layer 50 so as to cover the wiring layer 50, the adhesive layer 20 being made of the adhesive film. Note that the circuit board 200 may include any layer other than those described above. The first base material 11 in the circuit board 200 may have the same configuration as the insulating resin layer of the metal-clad laminate. The circuit board 200 can be manufactured by laminating an adhesive film to the side of the wiring layer 50 of a circuit board including the first base material 11 and the wiring layer 50 laminated on at least one surface of the first base material 11.
[0145] (Third aspect) As shown in FIG. 6, a circuit board 201 according to another embodiment of the present invention includes a first base material 11, a wiring layer 50 laminated on at least one surface of the first base material 11, an adhesive layer 20 laminated on the surface of the first base material 11 facing the wiring layer 50 so as to cover the wiring layer 50, and a second base material 12 laminated on the surface of the adhesive layer 20 opposite the first base material 11, and the adhesive layer 20 is made of the adhesive film. The circuit board 201 may include any layer other than those described above. The first base material 11 and the second base material 12 in the circuit board 201 may have the same configuration as the insulating resin layer of the metal-clad laminate. The circuit board 201 can be manufactured by bonding a second substrate 12 to the wiring layer 50 side of a circuit board having a first substrate 11 and a wiring layer 50 laminated on at least one surface of the first substrate 11 via an adhesive film.
[0146] (Fourth aspect) As shown in FIG. 7, the circuit board 202 according to another embodiment of the present invention includes a first base material 11, an adhesive layer 20 laminated on at least one surface of the first base material 11, a second base material 12 laminated on the surface of the adhesive layer 20 opposite the first base material 11, and wiring layers 50, 50 laminated on the surfaces of the first base material 11 and the second base material 12 opposite the adhesive layer 20, respectively, and the adhesive layer 20 is made of the adhesive film. The circuit board 202 may include any layer other than the above. The first base material 11 and the second base material 12 in the circuit board 202 may have the same configuration as the insulating resin layer of the metal-clad laminate. The circuit board 202 can be manufactured by preparing a first circuit board having a first substrate 11 and a wiring layer 50 laminated on at least one surface of the first substrate 11, and a second circuit board having a second substrate 12 and a wiring layer 50 laminated on at least one surface of the second substrate 12, and then placing an adhesive film between the first substrate 11 of the first circuit board and the second substrate 12 of the second circuit board and bonding them together.
[0147] [Multilayer circuit board] A multilayer circuit board according to an embodiment of the present invention includes a laminate in which a plurality of insulating resin layers are stacked, and one or more wiring layers embedded inside the laminate, and at least one of the plurality of insulating resin layers is formed of an adhesive layer 20 that has adhesiveness and covers the wiring layer, and the adhesive layer 20 is made of the adhesive film. Note that the multilayer circuit board of this embodiment may include any layer other than those described above. For example, as shown in FIG. 8, the multilayer circuit board 203 of the present embodiment has at least two insulating resin layers 34 and at least two wiring layers 50, and at least one of the wiring layers 50 is covered with an adhesive layer 20. The adhesive layer 20 covering the wiring layer 50 may partially cover the surface of the wiring layer 50, or may cover the entire surface of the wiring layer 50. The multilayer circuit board 203 may also have a wiring layer 50 exposed on the surface of the multilayer circuit board 203. The multilayer circuit board 203 may also have an interlayer connection electrode (via electrode) in contact with the wiring layer 50. The wiring layer 50 is formed by forming a conductor circuit in a predetermined pattern on one or both sides of the insulating resin layer 34. The conductor circuit may be patterned on the surface of the insulating resin layer 34, or may be patterned in a damascene (embedded) manner. The insulating resin layer 34 in the circuit board 203 may have the same configuration as the insulating resin layer of the metal-clad laminate.
[0148] The circuit board and multilayer circuit board of each of the above-described embodiments include the adhesive layer 20 containing adhesive polyimide with a controlled aromatic ring concentration, so that it is possible to reduce transmission loss even in high frequency transmission. EXAMPLES
[0149] The features of the present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to the examples. In the following examples, various measurements and evaluations are as follows, unless otherwise specified.
[0150] [Method for measuring amine value] Approximately 2 g of the dimer diamine composition is weighed into a 200-250 mL Erlenmeyer flask, and phenolphthalein is used as an indicator. A 0.1 mol / L ethanolic potassium hydroxide solution is dropped into the solution until the solution turns light pink, and the solution is dissolved in approximately 100 mL of neutralized butanol. 3-7 drops of phenolphthalein solution are added thereto, and titration is performed with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Five drops of bromophenol blue solution are added thereto, and titration is performed with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow. The amine value is calculated according to the following formula (1). Amine value = {(V2 x C2) - (V1 x C1)} x M KOH / m (1) Here, the amine value is expressed as mg-KOH / g, and M KOH is the molecular weight of potassium hydroxide, 56.1. V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent a 0.1 mol / L ethanolic potassium hydroxide solution and a 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.
[0151] [Measurement of weight average molecular weight (Mw) and number average molecular weight (Mn) of polyimide] Measurement was performed using a gel permeation chromatograph (manufactured by Tosoh Corporation, product name: HLC-8220GPC was used). Polystyrene was used as a standard substance, and tetrahydrofuran (THF) was used as a developing solvent.
[0152] [How to calculate fluoride concentration] The fluorine concentration is based on the molar ratio of monomers in the polyimide and means a percentage of the value obtained by dividing [atomic weight of fluorine atom×number of fluorine atoms] by the molecular weight of the entire polyimide structure.
[0153] [How to calculate CM value] The weight average molecular weight (Mw) of the polyimide and the weight content (C) of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide p ) the CM value was calculated based on the following formula: CM=(C p / Mw)×10 4 (i)
[0154] [Calculation of aromatic ring ratio in dimer diamine composition] The aromatic ring ratio of the dimer diamine composition was calculated by the following procedure. First, about 50 μl of the dimer diamine composition was dissolved in 550 μl of THF-d8 to prepare a sample. The prepared sample was subjected to liquid 1H-NMR measurement at room temperature using an FT-NMR device (manufactured by JEOL, product name: JNM-ECA400). The aromatic ring ratio was calculated according to the following formula from the ratio of the integral value of the 1H peak derived from the aromatic ring at 6.6 to 7.2 ppm to the integral value of the 1H peak derived from the CH2 group directly bonded to the NH2 group at 2.6 to 2.9 ppm. Aromatic ring ratio [mol%] = (Z / Y) × 100 [Here, Y means the integral value of the 1H peak (derived from the CH2 group directly bonded to the NH2 group) at 2.6 to 2.9 ppm, and Z means the integral value of the 1H peak (derived from the aromatic ring) at 6.6 to 7.2 ppm.]
[0155] [Calculation of GPC and chromatogram area percentage] (a) Dimer diamine (b) A monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group. (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group having 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (excluding the above-mentioned dimer diamine).
[0156] For GPC, 20 mg of the dimer diamine composition was pretreated with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of THF to prepare a 100 mg solution, which was then diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a Tosoh Corporation product name: HLC-8220GPC under the following conditions: column: TSK-gel G2000HXL, G1000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40° C., injection volume: 50 μL. Cyclohexanone was used as a standard substance to correct the elution time.
[0157] In this case, the retention times were adjusted so that the peak top of the cyclohexanone main peak was at a retention time of 27 to 31 minutes, and the period from the peak start to the peak end of the cyclohexanone main peak was 2 minutes, and the peak top of the main peak excluding the cyclohexanone peak was at a retention time of 18 to 19 minutes, and the period from the peak start to the peak end of the main peak excluding the cyclohexanone peak was 2 minutes to 4 minutes 30 seconds. (a) Component represented by the main peak; (b) A component represented by a GPC peak detected at a time later than the minimum retention time of the main peak; (c) Components represented by GPC peaks detected at earlier retention times than the minimum value of the main peak on the earlier side; was detected.
[0158] [Measurement of dielectric constant and dielectric tangent] The adhesive film was left for 24 hours under conditions of temperature: 23°C and humidity: 50 RH% using a vector network analyzer (manufactured by Agilent, product name: Vector Network Analyzer E8363C) and an SPDR resonator, and then the relative dielectric constant (ε) and dielectric loss tangent (Tan δ) at a frequency of 10 GHz were measured.
[0159] [Glass transition temperature (Tg)] The glass transition temperature (Tg) was measured using a thermomechanical analyzer (TMA: manufactured by Netsch, product name: TMA4000SA) for an adhesive film measuring 5 mm x 20 mm, at a heating rate of 5°C / min from 0°C to 300°C. The temperature at which the elongation changes during heating is defined as the glass transition temperature.
[0160] [Tensile modulus] The tensile modulus was measured by the following procedure. First, a test piece (width 12.7 mm × length 127 mm) was prepared from the adhesive film using a tension tester (manufactured by Orientec Co., Ltd., product name: Tensilon). Using this test piece, a tensile test was performed at 50 mm / min to determine the tensile modulus at 25°C.
[0161] [Warpage evaluation method] Warpage was evaluated using the following method. A polyimide solution was applied to a 25 μm thick polyimide film (manufactured by Toray DuPont, product name: Kapton 100EN) or a 12 μm thick copper foil so that the thickness after drying would be 25 μm, to prepare a test specimen. In this state, the polyimide film or copper foil was placed on the bottom, and the average height of the warpage at the four corners of the test specimen was measured, with a value of 5 mm or less being rated as "good" and a value of more than 5 mm being rated as "unacceptable."
[0162] [Measurement of storage modulus] Measurements were performed using a dynamic viscoelasticity measuring device (DMA: manufactured by TA Instruments, product name: RSA-G2).
[0163] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride 6FDA: 4,4'-(hexafluoroisopropylidene)diphthalic anhydride DDA: aliphatic diamine having 36 carbon atoms (manufactured by Croda Japan Co., Ltd., product name: PRIAMINE 1074, distilled and purified, amine value: 210 mg KOH / g, molecular weight: 534.29 (calculated from the amine value), mixture of dimer diamines having cyclic and chain structures, component (a): 97.9% by weight, component (b): 0.3%, component (c): 1.8%, aromatic ring ratio: 8.2 mol%) BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane HFBAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane TFMB: 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl N-12: Dodecanedioic acid dihydrazide NMP: N-methyl-2-pyrrolidone OP935: Aluminum salt of phosphinic acid (manufactured by Clariant, trade name: Exolit OP935, aluminum diethylphosphinate, phosphorus content 23%, average particle size 2 μm) SR-3000: Phosphate ester (manufactured by Daihachi Chemical Industry Co., Ltd., product name: SR-3000, non-halogen aromatic condensed phosphate ester, phosphorus content: 7.0%) The molecular weight of the above DDA was calculated by the following formula. Molecular weight = 56.1 x 2 x 1000 / amine value
[0164] [Example 1] A 1000 ml separable flask was charged with 36.23 g of BTDA (0.1122 mol), 53.95 g of DDA (0.1010 mol), 5.82 g of HFBAPP (0.0112 mol), 134.4 g of NMP, and 89.6 g of xylene, and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 5 hours, and 80.1 g of xylene was added to complete the imidization to obtain Polyimide Solution 1 (solid content: 30 wt %, weight average molecular weight: 47,617, fluorine concentration: 1.4, C p ;21.12%, CM value;4.4) was prepared.
[0165] [Examples 2 to 8] Polyimide solutions 2 to 8 were prepared in the same manner as in Example 1, except that the raw material compositions shown in Table 1 were used.
[0166] [Comparative Example 1] Polyimide solution 9 was prepared in the same manner as in Example 1, except that the raw material composition shown in Table 1 was used.
[0167] [Table 1]
[0168] [Example 9] The polyimide solution 1 was applied to one side of a release PET film 1 (Higashiyama Film Co., Ltd., product name: HY-S05, length x width x thickness = 200 mm x 300 mm x 25 μm), dried at 120°C for 10 minutes, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive film 9 having a thickness of 25 μm. The various evaluation results of the adhesive film 9 are as follows. ε; 2.7, Tan δ; 0.0016, Tg; 44℃, Tensile modulus; 440MPa, Thermoplastic
[0169] [Examples 10 to 16] Adhesive films 10 to 16 were obtained in the same manner as in Example 9, except for using polyimide solutions 2 to 8. The results of evaluation of various characteristics are shown in Table 2.
[0170] [Comparative Example 2] Adhesive film 17 was obtained in the same manner as in Example 9, except that polyimide solution 9 was used. The results of evaluation of various characteristics are shown in Table 2.
[0171] [Table 2]
[0172] [Example 17] 1.1 g of N-12 (0.004 mol) was mixed with 100 g of polyimide solution 1 (30 g as solid content), diluted with 7.5 g of OP935 and 14.0 g of xylene, and further stirred for 1 hour to prepare adhesive composition 17.
[0173] [Examples 18 to 23] Adhesive compositions 18 to 23 were prepared in the same manner as in Example 17, except that polyimide solutions 2 to 7 were used.
[0174] [Example 24] 1.1 g of N-12 (0.004 mol) was mixed with 100 g of polyimide solution 5 (30 g as solid content), diluted with 6.0 g of SR-3000 and 14.0 g of xylene, and further stirred for 1 hour to prepare adhesive composition 24.
[0175] [Example 25] The adhesive composition 17 was applied to one side of a release PET film 1 and dried at 80°C for 15 minutes to obtain a resin sheet 24 having an adhesive layer thickness of 25 μm. The adhesive layer was then peeled off from the release PET film 1 to obtain an adhesive film 25 having a thickness of 25 μm.
[0176] [Examples 26 to 32] Resin sheets 26 to 32 were obtained in the same manner as in Example 25 except that adhesive compositions 18 to 24 were used, and then adhesive films 26 to 32 were obtained.
[0177] [Example 33] The adhesive composition 17 was applied to one side of a polyimide film 1 (manufactured by DuPont-Toray Co., Ltd., product name: Kapton 50EN, ε=3.6, tan δ=0.0084, length×width×thickness=200 mm×300 mm×12 μm) and dried at 80° C. for 15 minutes to obtain a coverlay film 33 with an adhesive layer thickness of 25 μm. The warpage state of the obtained coverlay film 33 was "good".
[0178] [Examples 34 and 35] Coverlay films 34 and 35 were obtained in the same manner as in Example 33, except that adhesive composition 19 or 24 was used. The warpage state of the obtained coverlay films 34 and 35 was both "good".
[0179] [Example 36] The release PET film 1 was laminated so as to be in contact with the adhesive layer side of the coverlay film 33, and pressure-bonded for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator. Thereafter, the adhesive composition 17 was applied to the polyimide film 1 side of the coverlay film 33 in a state in which the release PET film 1 was pressure-bonded, so that the thickness after drying was 25 μm, and dried at 80°C for 15 minutes. The release PET film 1 was laminated so as to be in contact with the surface on which the adhesive composition 17 was applied and dried, and pressure-bonded for 2 minutes at a temperature of 160°C and a pressure of 0.8 MPa using a vacuum laminator, to obtain a polyimide adhesive laminate 36 having adhesive on both sides of the polyimide film.
[0180] [Examples 37 and 38] Polyimide adhesive laminates 37 and 38 were obtained in the same manner as in Example 36, except that coverlay films 34 and 35 were used and adhesive composition 19 or 24 was applied.
[0181] [Example 39] The adhesive composition 17 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 15 minutes to obtain a resin-coated copper foil 39 having an adhesive layer thickness of 25 μm. The warpage state of the resin-coated copper foil 39 obtained was “good”.
[0182] [Examples 40 and 41] Resin-coated copper foils 40 and 41 were obtained in the same manner as in Example 39, except that adhesive composition 19 or 24 was used. The warpage state of the obtained resin-coated copper foils 40 and 41 was both "good".
[0183] [Example 42] The adhesive composition 17 was applied to one side of an electrolytic copper foil having a thickness of 12 μm and dried at 80° C. for 30 minutes to obtain a resin-coated copper foil 42 having an adhesive layer thickness of 50 μm. The warpage state of the resin-coated copper foil 42 obtained was “good”.
[0184] [Example 43] The adhesive composition 17 was further applied to the surface of the adhesive layer of the resin-coated copper foil 42 and dried at 80°C for 30 minutes to obtain a resin-coated copper foil 43 having an adhesive layer with a total thickness of 100 µm. The warpage state of the obtained resin-coated copper foil 43 was "good".
[0185] [Example 44] The adhesive composition 17 was applied to one side of a release PET film 1, dried at 80° C. for 30 minutes, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive film 44 with a thickness of 50 μm.
[0186] [Example 45] On a 12 μm thick electrolytic copper foil, an adhesive film 44, a polyimide film 2 (manufactured by DuPont, product name: Kapton 100-EN, thickness 25 μm, ε1 = 3.6, tan δ1 = 0.0084), an adhesive film 44 and a 12 μm thick electrolytic copper foil were laminated in that order, and the laminate was pressed using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa for 2 minutes. The temperature was then increased from room temperature to 160°C, and the laminate was heat-treated at 160°C for 4 hours, to obtain a copper-clad laminate 45.
[0187] [Examples 46 and 47] Adhesive films 46 and 47 with a thickness of 50 μm were obtained in the same manner as in Example 44, except that adhesive composition 19 or 24 was used.
[0188] [Examples 48 and 49] Copper-clad laminates 48 and 49 were obtained in the same manner as in Example 45, except that adhesive films 46 and 47 were used.
[0189] [Example 50] The coverlay film 33 was laminated onto a 12 μm thick electrolytic copper foil so that the adhesive layer side was in contact with the copper foil, and then pressed using a vacuum laminator at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes.Then, the temperature was increased from room temperature to 160° C. and heat-treated at 160° C. for 2 hours to obtain a copper-clad laminate 50.
[0190] [Examples 51 and 52] Copper-clad laminates 51 and 52 were obtained in the same manner as in Example 50, except that coverlay films 34 and 35 were used.
[0191] [Example 53] An adhesive film 25 was laminated on a 12 μm thick rolled copper foil, and the polyimide film side of the coverlay film 33 was laminated so that it was in contact with the adhesive film 25. Further, a 12 μm thick rolled copper foil was laminated in sequence on the adhesive layer side of the coverlay film 33, and the laminate was pressed using a vacuum laminator at a temperature of 160° C. and a pressure of 0.8 MPa for 2 minutes. The temperature was then increased from room temperature to 160° C., and the laminate was heat-treated at 160° C. for 2 hours to obtain a copper-clad laminate 53.
[0192] [Examples 54 and 55] Copper-clad laminates 54 and 55 were produced in the same manner as in Example 51, except that adhesive film 25 was replaced with adhesive films 27 and 32, respectively, and coverlay film 33 was replaced with coverlay films 34 and 35, respectively.
[0193] [Example 56] Two sheets of resin-coated copper foil 43 were prepared, and laminated so that the adhesive layer sides of the two resin-coated copper foils 43 were in contact with a polyimide film 3 (manufactured by DuPont, product name: Kapton 200-EN, thickness 50 μm, ε = 3.6, tan δ = 0.0084). The sheets were then pressed together using a vacuum laminator at a temperature of 160°C and a pressure of 0.8 MPa for 5 minutes, after which the temperature was increased from room temperature to 160°C and heat-treated at 160°C for 4 hours to obtain a copper-clad laminate 56.
[0194] [Example 57] The adhesive composition 24 was applied to the polyimide side of a single-sided copper-clad laminate 1 (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: Espanex MC12-25-00UEM, length x width x thickness = 200 mm x 300 mm x 25 μm), and dried at 80 ° C for 30 minutes to obtain an adhesive-coated copper-clad laminate 57 with an adhesive layer thickness of 50 μm. The single-sided copper-clad laminate 1 was laminated so that the resin layer side of the single-sided copper-clad laminate 1 was in contact with the adhesive layer side of the adhesive-coated copper-clad laminate 57, and the laminate was pressed at a temperature of 160 ° C, a pressure of 4.0 MPa, for 120 minutes using a small precision press to obtain a copper-clad laminate 57.
[0195] [Example 58] Two adhesive-attached copper-clad laminates 57 were laminated together with their adhesive layer sides in contact, and pressed together using a small precision press at a temperature of 160° C. and a pressure of 4.0 MPa for 120 minutes to obtain copper-clad laminate 58.
[0196] [Example 59] An adhesive film 44 was laminated on the resin layer side of the single-sided copper-clad laminate 1, and then another adhesive film 44 was laminated on top of that so that the resin layer side of the single-sided copper-clad laminate 1 was in contact with the adhesive film 44. The laminate was then pressed using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain a copper-clad laminate 59.
[0197] [Example 60] The adhesive composition 17 was applied to one side of a release PET film 1, dried at 80° C. for 15 minutes, and the adhesive layer was peeled off from the release PET film 1 to obtain an adhesive film 60 with a thickness of 15 μm.
[0198] [Example 61] An adhesive film 60 was laminated on the resin layer side of single-sided copper-clad laminate 1, and then another adhesive film 60 was laminated on top of that so that the resin layer side of single-sided copper-clad laminate 1 was in contact with adhesive film 60. The laminate was then pressed using a small precision press at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain copper-clad laminate 61.
[0199] [Example 62] A double-sided copper-clad laminate 2 (product name: ESPANEX MB12-25-00UEG, manufactured by Nippon Steel Chemical & Material Co., Ltd.) was prepared, and the copper foil on one side was subjected to circuit processing by etching to form a conductor circuit layer, thereby obtaining a wiring board 62A.
[0200] The copper foil on one side of the double-sided copper-clad laminate 2 was removed by etching to obtain a copper-clad laminate 62B.
[0201] An adhesive film 25 was sandwiched between the conductive circuit layer side of wiring board 62A and the resin layer side of copper-clad laminate 62B, and the laminated bodies were thermocompression bonded at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain multilayer circuit board 62.
[0202] [Example 63] A copper-clad laminate 63 was prepared using an insulating substrate made of a liquid crystal polymer film (manufactured by Kuraray Co., Ltd., product name: CT-Z, thickness: 50 μm, CTE: 18 ppm / K, heat distortion temperature: 300° C., ε=3.40, tan δ=0.0022) with 18 μm-thick electrolytic copper foil provided on both sides thereof. The copper foil on one side was subjected to circuit processing by etching to obtain a wiring board 63A having a conductor circuit layer formed thereon.
[0203] The copper foil on one side of the copper-clad laminate 63 was removed by etching to obtain a copper-clad laminate 63B.
[0204] An adhesive film 44 was sandwiched between the conductive circuit layer side of wiring board 63A and the insulating base material layer side of copper-clad laminate 63B, and the laminated bodies were thermocompression bonded at a temperature of 160°C and a pressure of 4.0 MPa for 120 minutes to obtain multilayer circuit board 63.
[0205] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]
[0206] REFERENCE SIGNS LIST 10...substrate, 11...first substrate, 12...second substrate, 20...adhesive layer, 30, 33, 34...insulating resin layer, 31...first insulating resin layer, 32...second insulating resin layer, 41...first single-sided metal-clad laminate, 42...second single-sided metal-clad laminate, 50...wiring layer, M...metal layer, M1...first metal layer, M2...second metal layer, 100...laminate, 101...three-layer metal-clad laminate, 102...laminated metal-clad laminate, 103...metal-clad laminate with adhesive layer, 200, 201, 202...circuit board, 203...multilayer circuit board
Claims
1. A polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component, The following conditions a to c: a) containing a fluorine atom-containing tetracarboxylic acid residue and / or a fluorine atom-containing diamine residue, and the total content of the fluorine atoms relative to the total content of all atoms in the polyimide is within the range of 1% by weight or more and 12% by weight or less; b) containing diamine residues derived from aliphatic diamines in an amount of 60 to 99 mol % relative to the total diamine residues; c) being a thermoplastic polyimide; and satisfy the following formula (i): CM value = (C / Mw) x 10 4 ... (i) [In the formula, C represents the weight content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide, and Mw represents the weight average molecular weight of the polyimide.] The polyimide is characterized in that the CM value, which is an index representing the amount of 6-membered aromatic rings contained in the polyimide, is within the range of 3 to 38, as calculated based on the following formula:
2. 2. The polyimide according to claim 1, wherein the aliphatic diamine is a dimer diamine composition mainly composed of a dimer diamine obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups.
3. 2. The polyimide according to claim 1, having a weight average molecular weight in the range of 5,000 to 200,000.
4. 2. The polyimide according to claim 1, wherein the content of carbon atoms derived from a 6-membered aromatic ring (excluding the carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide is within the range of 12 to 40% by weight.
5. A polyimide solution comprising the polyimide according to claim 1 and a solvent capable of dissolving the polyimide.
6. A polyimide film comprising, as a resin component, a polyimide containing a tetracarboxylic acid residue derived from a tetracarboxylic acid anhydride component and a diamine residue derived from a diamine component, The polyimide contains a tetracarboxylic acid residue containing a fluorine atom and / or a diamine residue containing a fluorine atom, and the total content of the fluorine atoms is within a range of 1% by weight to 12% by weight based on the total content of all atoms in the polyimide, and contains diamine residues derived from an aliphatic diamine within a range of 60 to 99 mol % based on the total diamine residues, and is represented by the following mathematical formula (i): CM value = (C / Mw) x 10 4 ... (i) [In the formula, C represents the weight content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide, and Mw represents the weight average molecular weight of the polyimide.] The polyimide has a CM value, which is an index representing the amount of 6-membered aromatic rings contained in the polyimide, calculated based on the following formula: A polyimide film having a dielectric loss tangent (Tan δ) of less than 0.002 at 10 GHz as measured by a split post dielectric resonator (SPDR) after being conditioned for 24 hours under constant temperature and humidity conditions (normal state) of 23°C and 50% RH.
7. 7. The polyimide film according to claim 6, wherein the aliphatic diamine is a dimer diamine composition mainly composed of a dimer diamine obtained by substituting two terminal carboxylic acid groups of a dimer acid with primary aminomethyl groups or amino groups.
8. 7. The polyimide film according to claim 6, wherein the weight average molecular weight of the polyimide is within the range of 5,000 to 200,000.
9. 7. The polyimide film according to claim 6, wherein the content of carbon atoms derived from a 6-membered aromatic ring (excluding carbon atoms of the 6-membered aromatic ring derived from the dimer diamine composition) relative to the total content of all atoms in the polyimide is within a range of 12 to 40% by weight.
10. An adhesive film comprising the polyimide film according to claim 6.
11. A laminate having a substrate and an adhesive layer laminated on at least one surface of the substrate, A laminate, wherein the adhesive layer comprises the adhesive film according to claim 10.
12. A coverlay film having a coverlay film material layer and an adhesive layer laminated on the coverlay film material layer, A coverlay film, wherein the adhesive layer is the adhesive film according to claim 10.
13. A resin-coated copper foil in which an adhesive layer and a copper foil are laminated, A resin-coated copper foil, wherein the adhesive layer is made of the adhesive film according to claim 10.
14. A metal-clad laminate having an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, A metal-clad laminate, wherein at least one of the insulating resin layers is made of the adhesive film according to claim 10.
15. A metal-clad laminate having an insulating resin layer, an adhesive layer laminated on at least one surface of the insulating resin layer, and a metal layer laminated on the insulating resin layer via the adhesive layer, A metal-clad laminate, wherein the adhesive layer comprises the adhesive film according to claim 10.
16. A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one surface of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one surface of the second metal layer; An adhesive layer is disposed so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate, A metal-clad laminate, wherein the adhesive layer comprises the adhesive film according to claim 10.
17. A metal-clad laminate comprising: a single-sided metal-clad laminate having an insulating resin layer and a metal layer laminated on one side of the insulating resin layer; and an adhesive layer laminated on the other side of the insulating resin layer, the adhesive layer being made of the adhesive film described in claim 10.
18. A circuit board obtained by wiring the metal layer of the metal-clad laminate according to claim 14.
19. A circuit board comprising: a first base material; a wiring layer laminated on at least one surface of the first base material; and an adhesive layer laminated on a surface of the first base material facing the wiring layer so as to cover the wiring layer, A circuit board, wherein the adhesive layer comprises the adhesive film according to claim 10.
20. A circuit board comprising: a first base material; a wiring layer laminated on at least one surface of the first base material; an adhesive layer laminated on a surface of the first base material facing the wiring layer so as to cover the wiring layer; and a second base material laminated on a surface of the adhesive layer opposite to the first base material, A circuit board, wherein the adhesive layer comprises the adhesive film according to claim 10.
21. A circuit board comprising: a first base material; an adhesive layer laminated on at least one surface of the first base material; a second base material laminated on a surface of the adhesive layer opposite to the first base material; and wiring layers laminated on each of the first base material and the second base material opposite to the adhesive layer, A circuit board, wherein the adhesive layer comprises the adhesive film according to claim 10.
22. A multilayer circuit board comprising a laminate including a plurality of laminated insulating resin layers, and at least one wiring layer embedded in the laminate, At least one of the plurality of insulating resin layers is formed of an adhesive layer having adhesiveness and covering the wiring layer, A multilayer circuit board, wherein the adhesive layer comprises the adhesive film according to claim 10.
Citation Information
Patent Citations
Crosslinked polyimide resin, adhesive resin composition and cured product thereof, cover lay film and circuit board
JP2013001730A
Solvent-soluble polyimide resin, method for producing the same, polyimide composition containing the polyimide resin, polyimide film and coated article
JP2013155329A
Circuit board
JP2016192531A
Metal-clad laminate, adhesive sheet, adhesive polyimide resin composition, and circuit board
JP2018140544A
Diamine compound as polyimide raw material for forming photoelectric display device, polyamide acid and polyimide using the same
JP2019119755A